Literary Sentiments in the Vernacular: Gender and Genre in Modern South Asia. Issue 5 (2nd September 2020) - Gupta, Charu; Brueck, Laura; Harder, Hans; Nijhawan, Shobna
Abstract: This collection brings together nine essays, accompanied by nine short translations, that redraw the boundaries of literary histories both temporally and spatially. The essays, rooted in the humanities and informed by interdisciplinary area studies, explore multiple linkages between forms of print culture, linguistic identities and diverse vernacular literary spaces in colonial and post-colonial South Asia. The essays and translations foreground complex and politicised expressions of gender and genre in fictional and non-fictional print materials and thus draw meaningful connections between the vernacular and literature, the everyday and the marginals, and gender and sentiment. Collectively, they expand vernacular literary archives, canons and genealogies, and push us to theorise the nature of writing in South Asia.